2020
DOI: 10.34172/apb.2021.003
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Ocular Novel Drug Delivery Systems of Antifungal Drugs: Functional Evaluation and Comparison of Conventional and Novel Dosage Forms

Abstract: Ocular fungal infections affect more than one million people annually worldwide. They can lead to impaired vision or even complete blindness, so they should be treated immediately to prevent such consequences. Although topical administration has always been the most common route of ocular drug delivery owing to high patient acceptance, reduced side effects, and the possibility of self-administration, its limited ocular bioavailability poses a major challenge. As a result, attention has recently been drawn to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 67 publications
0
25
0
2
Order By: Relevance
“…It has been shown that NDDSs may enhance the water-solubility of lipophilic drugs and prolong the amount of their time on the ocular surface by virtue of their mucoadhesive nature and ability to promote sustained drug release [ 5 , 6 , 7 ]. Previous studies have demonstrated the efficacy and benefits of these systems for ocular delivery of antibacterial, antifungal, and anti-inflammatory agents [ 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that NDDSs may enhance the water-solubility of lipophilic drugs and prolong the amount of their time on the ocular surface by virtue of their mucoadhesive nature and ability to promote sustained drug release [ 5 , 6 , 7 ]. Previous studies have demonstrated the efficacy and benefits of these systems for ocular delivery of antibacterial, antifungal, and anti-inflammatory agents [ 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…12 These systems have many advantages like high surface-area-to-volume ratio and high porosity; leading to high ability of the nanofibers to increase solubility, helping the controlled release of drug, and increasing intraocular bioavailability of drugs. 13,14 Based on the previous studies, the cornea and conjunctiva have a negatively charged structure. Hence, positively charged mucoadhesive polymeric carriers interacting with the cornea and conjunctiva could increase contact time and consequently, concentration of drugs in the cornea.…”
Section: Introductionmentioning
confidence: 99%
“… 12 These systems have many advantages like high surface-area-to-volume ratio and high porosity; leading to high ability of the nanofibers to increase solubility, helping the controlled release of drug, and increasing intraocular bioavailability of drugs. 13 , 14 …”
Section: Introductionmentioning
confidence: 99%
“…have been designed and developed mostly utilizing nanotechnology to improve the ocular delivery of various drugs. [6][7][8][9] Corneal permeability is an effective factor in the determination of the therapeutic efficacy of topical preparations. Many drugs need to pass through the cornea to arrive at their site of action for a therapeutical effect.…”
Section: Introductionsmentioning
confidence: 99%